2015
DOI: 10.1186/s40001-015-0193-6
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of stress fractures of the foot using PET-MRI: a feasibility study

Abstract: BackgroundDiagnosis and treatment of stress fractures still remains to be a clinical and radiological challenge. Therapeutic options vary from conservative treatment to surgical treatment without a clear treatment concept. Recently the combination of PET and MRI has been introduced, aiming a superior diagnostic accuracy in clinical practice. Therefore the aim of our study was to analyse whether PET-MRI would be a feasible technique to recognize stress fractures of the foot and to analyse if our conservative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
(53 reference statements)
0
8
0
1
Order By: Relevance
“…9). 145 A separate study in patients with foot pain of unclear cause showed that in cases of stress fracture, PET-MRI performed better than PET/CT due to earlier depiction of T 1 -weighted MRI changes than changes on CT, which provided higher diagnostic confidence. 146 Overall, the authors saw that 18 F-NaF PET-MRI provided more diagnostic information and higher diagnostic confidence compared with PET/CT for evaluation of foot pain of unclear cause.…”
Section: Other Nononcologic Musculoskeletal Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…9). 145 A separate study in patients with foot pain of unclear cause showed that in cases of stress fracture, PET-MRI performed better than PET/CT due to earlier depiction of T 1 -weighted MRI changes than changes on CT, which provided higher diagnostic confidence. 146 Overall, the authors saw that 18 F-NaF PET-MRI provided more diagnostic information and higher diagnostic confidence compared with PET/CT for evaluation of foot pain of unclear cause.…”
Section: Other Nononcologic Musculoskeletal Applicationsmentioning
confidence: 99%
“…PET‐MRI was shown to be useful for diagnosis of stress fractures and stress reactions in cases where no pathological findings were present on X‐ray (Fig. ) . A separate study in patients with foot pain of unclear cause showed that in cases of stress fracture, PET‐MRI performed better than PET/CT due to earlier depiction of T 1 ‐weighted MRI changes than changes on CT, which provided higher diagnostic confidence .…”
Section: Other Nononcologic Musculoskeletal Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of imaging stress fractures with NaF-PET/ MR was investigated in 20 patients with foot pain by Crö nlein and colleagues. 24 Despite negative findings on radiography, 4 stress fractures and 7 stress reactions involving the foot and ankle were identified by PET/MR. A comparative study between PET/CT and PET/MR by the same group found that both hybrid modalities identified the same 42 lesions across 22 subjects with foot pain of unclear cause.…”
Section: Musculoskeletal Traumamentioning
confidence: 99%
“…Additionally, 18 F-NaF has been shown to detect increased bone turnover at areas of new bone formation around stress fractures. It was demonstrated that PET-MRI may be able to diagnose stress fractures and stress reactions in cases where no pathological findings are present on X-ray (32). These studies collectively demonstrate that 18 F-NaF can be a useful marker for the assessment of bone turnover to study metabolic bone diseases.…”
Section: Tracersmentioning
confidence: 99%